Microsoft SQL Server 2008 Integration Services problem-design-solution - Veerman, Erik, 1973- (Wrox problem--design--solution., 2009)
An authoritative guide to designing effective solutions for data cleansing, ETL, and file management with SQL Server 2008 Integration Services SQL Server Integration Services (SSIS) is the leading tool in the data warehouse industry, used for performing extraction, transformation, and load operations. After an overview of SSIS architecture, the authors walk you a series of real-world problems and show various techniques for handling them. Shows you how to design SSIS solutions for data cleansing, ETL and file managementDemonstrates how to integrate data from a var.